Kompetensi Pengguna dan Program Partnership dalam Mempengaruhi Pengambilan Keputusan melalui Implementasi Sistem Informasi Akuntansi - Amarina, Dina; Fitrios, Ruhul; Supriono, Supriono (Jurnal Akuntansi dan Governance, 2024)
Objectives: This study seeks to validate the impact of user competency and partnership programs on decision-making through the implementation of an Accounting Information System (AIS).Design/method/approach: Employing a quantitative approach, the research focuses on Pekanbaru City Micro, Small, and Medium Enterprises (MSMEs), utilizing purposive sampling for sample selection. Primary data are collected through a questionnaire, and data analysis involves descriptive methods and Partial Last Square (PLS) data analysis.Results/findings: The study reveals that the knowledge and skills possessed by AIS users contribute to enhanced AIS application in MSMEs, facilitating the timely, routine, accurate, and comprehensive generation of financial information or reports aligned with user needs. The competence of AIS users also positively impacts decision-making, enabling MSMEs to establish goals, provide alternatives, minimize uncertainty, and evaluate decisions made. However, the partnership program associated with AIS in Pekanbaru City MSMEs is currently suboptimal, exhibiting no significant effect on AIS implementation.Theoretical contribution: This study explores the novel examination of the impact of a partnership program on decision-making through the implementation of an accounting information system..Practical contribution: The findings indicate that the existing partnership program does not influence AIS implementation. Thus, government or related institutions can enhance similar programs by prioritizing improvements in AIS implementation.Limitations: The study's limitations include the non-classification of MSMEs into micro, small, and medium categories during questionnaire distribution and a sample size comprising only 83%.